The Williamsburg Charter: A Guideline for Democratic and Civil Debate About Religion - Dugan, Robert P. (Journal of law and religion, 1990)
Early in the seventeenth century, under pressure to conform to the Established Church, an evangelical English pastor fled with his congregation to Leyden, Holland. Pastor John Robinson was the only forebear of mine who, to my knowledge, was a minister. Eventually, he would remain in Holland while others of his people sailed to the New World on the Mayflower.Robinson's hunger for religious liberty was shared by enough of our Founding Fathers that they crafted a nation characterized by religious liberty. Thanks to the genius of the First Amendment Religious Liberty clause, the United States is today the destiny of choice for refugees fleeing religious persecution. The Williamsburg Charter has forced us to rethink some first principles which we have taken too much for granted, and others in which our thinking may have gone slightly off course. In these brief remarks, let me focus on the third guideline "for conducting public debates involving religion in a manner that is democratic and civil."